Our good neighbors: Understanding ecosystem services provided by insectivorous bats in Rwanda. - Olivier Nsengimana; Faith M Walker; Paul W Webala; Innocent Twizeyimana; Marie-Claire Dusabe; Daniel E Sanchez; Colin J Sobek; Deo Ruhagazi; Peace Iribagiza; Richard Muvunyi; Rodrigo A Medellin (PLoS ONE, 2023)
Bats are prodigious consumers of agricultural and forest pests, and are, therefore, a natural asset for agricultural productivity, suppressing populations of such pests. This study provides baseline information of diet of 143 bats belonging to eight insectivorous bat species from agricultural areas of Rwanda while evaluating the effectiveness of bats as pest suppressors. Using DNA metabarcoding to analyze bat fecal pellets, 85 different insect species were detected, with 60% (n = 65), 64% (n = 11) and 78% (n = 9) found to be agricultural pests from eastern, northern and western regions, respectively. Given the high percentages of agricultural pests detected, we submit that Rwandan insectivorous bats have the capacity for biocontrol of agricultural pests. Rwandan bat populations should be protected and promoted since they may foster higher crop yields and sustainable livelihoods.